Transformative Education in Character Development of Students in Religious-Based Schools: Narrative Review - Megawati, Megawati; Sulisworo, Dwi (ITScience (Information Technology and Science), 2024)
This article explores and analyzes various transformative education approaches implemented in religious-based schools and their impact on character formation in students. The method used in this research is a narrative review involving the collection, synthesis, and analysis of current literature on character education, principles of transformative education, and best practices in religious-based schools. This review encompasses various sources, including scholarly journals, books, and relevant research reports, to provide a comprehensive overview of how transformative education can be integrated into the curriculum and educational practices within a religious-based environment. The study results indicate that transformative education emphasizes mastery of subject matter and prioritizes spiritual and ethical values that contribute to student character development. Several key aspects of transformative education identified in this research include a focus on social interaction, reflective processes, and active student engagement in the learning process. Inclusive teaching methods, group discussions, and community-based projects are among the practices that support the holistic formation of students' character. The findings of this study also demonstrate that implementing transformative education within the context of religious education can produce more responsible, empathetic, and high-integrity individuals. Furthermore, transformative education aids students in understanding and appreciating differences, which is essential in a diverse society. Hopefully, These findings will provide educators, school administrators, and policymakers with insights into formulating effective strategies to strengthen character education in religious-based schools and create a better learning environment.